Komunikasi Positif Dalam Pengasuhan Anak Usia Dini - Isna Siskawati (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this study is to recommend readers to change their parenting communication style from traditional communication style to positive communication. Qualitative research methods with a library study approach. Data collection techniques with documentation. Data reduction processing techniques, presentation and conclusion. The results of the study show: positive communication steps in early childhood care are obtained: (1) leaving traditional communication styles: by changing the message of communication to children. (2) use the message "I" to convey thoughts and feelings: serves to convey facts (3) reads children's body language: understands children's movements (4) becomes an active listener: respects children's opinions and words. (5). Change negative language to positive language: to change a child's bad habits.